EMPLOYER-UNIVERSITY INTERACTIONS AS LEADING APPROACH IN TEACHING QUALITY IMPROVEMENT – RESULTS OF BG051PO001-3.1.07-0041 EDUCOMP PROJECT - Vatchkova, Elizabeth; Popova, Radostina; Neykov, Nikolay (Innovation in Woodworking Industry and Engineering design, 2015)
The productive interaction between employers and university in almost each level in the University of Forestry is a part of basic approaches for gaining competitive advantages in the competitive struggle to attract students. Project BG051PO001-3.1.07-0041 EDUCOMP achieved spectacular results in that matter. In current paper an attempt is made for presenting the leading results of the project that influence the quality of interactions which could improve the quality of educational programs.